2022
DOI: 10.1093/ije/dyac173
|View full text |Cite
|
Sign up to set email alerts
|

Asthma inflammatory phenotypes on four continents: most asthma is non-eosinophilic

Abstract: Background Most studies assessing pathophysiological heterogeneity in asthma have been conducted in high-income countries (HICs), with little known about the prevalence and characteristics of different asthma inflammatory phenotypes in low-and middle-income countries (LMICs). This study assessed sputum inflammatory phenotypes in five centres, in Brazil, Ecuador, Uganda, New Zealand (NZ) and the United Kingdom (UK). Methods We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Asthma is a heterogeneous pulmonary disease comprised of several different endotypes which depict various pathways of the inflammatory and immune response [38]. In general, most of the current research concentrates on eosinophilic airway inflammation, with poor knowledge of principal causes and mechanisms related to non-eosinophilic phenotypes, which are less receptive to inhaled corticosteroids (ICS), the current treatment of choice for asthma [39][40][41]. In the present study, we demonstrated that sphingolipid metabolism is abnormal in asthmatic patients, whereas sphingosine metabolites, altered largely in the untargeted lipidomics analysis, failed to distinguish between the different endotypes of asthma both in plasma and induced sputum in the targeted lipidomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a heterogeneous pulmonary disease comprised of several different endotypes which depict various pathways of the inflammatory and immune response [38]. In general, most of the current research concentrates on eosinophilic airway inflammation, with poor knowledge of principal causes and mechanisms related to non-eosinophilic phenotypes, which are less receptive to inhaled corticosteroids (ICS), the current treatment of choice for asthma [39][40][41]. In the present study, we demonstrated that sphingolipid metabolism is abnormal in asthmatic patients, whereas sphingosine metabolites, altered largely in the untargeted lipidomics analysis, failed to distinguish between the different endotypes of asthma both in plasma and induced sputum in the targeted lipidomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that asthma is not uniform across the globe and failure to validate the importance of a gene across ethnic groups may reflect the diversity of asthma, and not a false positive finding in a single population. 103 Current understanding of GWAS is that to detect subtle effects of common genetic variants that have previously gone undetected, it is necessary to use larger sample sizes. In recent years, there has been a significant increase in the establishment of international consortiums, with collaboration playing a central role in conducting research.…”
Section: Pregnancymentioning
confidence: 99%
“…In the field of epidemiology, it is commonly accepted that when several investigative teams, in various populations, using diverse designs and methods, consistently observe relationships between covariates, it is considered as proof that the association is not a result of chance or error. However, it should be noted that asthma is not uniform across the globe and failure to validate the importance of a gene across ethnic groups may reflect the diversity of asthma, and not a false positive finding in a single population 103 . Current understanding of GWAS is that to detect subtle effects of common genetic variants that have previously gone undetected, it is necessary to use larger sample sizes.…”
Section: Gene–environment–time Interactions In Asthma Developmentmentioning
confidence: 99%
“…The number of people with bronchial asthma continued to increase by 0.5% in 2018. This disease causes narrowing of the airways due to hyperactivity, which leads to disrupted breathing patterns and decreased oxygen levels [2] [3]. Individuals with asthma experience increased resistance in the smaller airways to expiratory airflow, thus requiring more time to exhale their entire vital capacity (FVC) [4] [5].…”
Section: Introductionmentioning
confidence: 99%